Analisis Dampak Kompensasi, Keselamatan Kerja dan Kesehatan terhadap Kinerja Karyawan PT Anugerah Sinar Mustika (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the effect of compensation, occupational safety, and health on employee performance at PT Anugerah Sinar Mustika. The background of the study is based on the issue of employee dissatisfaction with compensation, increasing work accident rates, and high absenteeism due to health problems. The research method used is quantitative with multiple linear regression analysis of 80 respondents. The results of the simultaneous test (F test) show that compensation, occupational safety, and health together have a significant effect on employee performance (F count = 20.214; sig. = 0.000). Partially (t test), occupational safety and health variables have a positive and significant effect on performance, while compensation does not have a significant effect. The Adjusted R² value of 0.422 indicates that 42.2% of employee performance variations can be explained by these three variables. These findings are expected to be evaluation materials for companies in formulating performance improvement strategies through improving occupational safety and health aspects.